ANALYSIS CONCENTRATION OF SURFACTANT ANIONIC AND THE RELATION WITH DIATOM ABUNDANCE IN BUNGUS WATER, PADANG WEST SUMATERA - Putri, Rukiana Audi; Nedi, Syahril; Nurrachmi, Irvina (Asian Journal of Aquatic Sciences, 2020)
This research aims to analyze surfactant anionic concentration and diatom abundance that has been implemented at May 2018 in Bungus rivers, Padang. This Research were conducted in survey method, four station were eshtablished with three replication of each sampling station. Analysis of surfactant anionic and diatom content was done at Chemistry Oceanography Laboratory and diatom identification was performed at Biology Oceanography Laboratory. The results showed that surfactant content in the waters ranged from 0,309-0,773 ppm and diatom abundance based on laboratory test on ranged 40,7407-81,4815 Ind/l. The correlation of surfactant and diatom content in waters by using linear regression y = Y = 94.56 -66.8x with correlation coefficient r = 0,809 and correlation water quality parameters with diatom abundance by using multiple linear regression Y= 787,189 -238,828X1 -9,032X2 -6,185X3 +5,371X4 +303,081X5 -35,631X6 with determination regression 0,995 and correlation coefficient r = 0,997.